Non-technical skills assessment for prelicensure nursing students: An integrative review. (November 2017) - Pires, Sara; Monteiro, Sara; Pereira, Anabela; Chaló, Daniela; Melo, Elsa; Rodrigues, Alexandre
Abstract: Background: In nursing, non-technical skills are recognized as playing an important role to increase patient safety and successful clinical outcomes (Pearson and McLafferty, 2011 ). Non-technical skills are cognitive and social resource skills that complement technical skills and contribute to safe and efficient task performance (Flin et al., 2008 ). In order to effectively provide non-technical skills training, it is essential to have an instrument to measure these skills. Methodology: An online search was conducted. Articles were selected if they referred to and/or described instruments assessing non-technical skills for nurses and/or prelicensure nursing students in educational, clinical and/or simulated settings with validation evidence (inclusion criteria). Results: Of the 53 articles located, 26 met the inclusion criteria. Those referred to and/or described 16 instruments with validation evidence developed to assess non-technical skills in multidisciplinary teams including nurses. Conclusion: Although articles have shown 16 valid and reliable instruments, to our knowledge, no instrument has been published or developed and validated for the assessment of non-technical skills of only nurses in general, relevant for use in high-fidelity simulation-based training for prelicensure nursing students. Therefore, there is a need for the development of such an instrument. Highlights: Patient safety and the incidence of errors are important issues in healthcare. One of the most important strategies for error reduction involves prevention. Non-technical skills learning and training in healthcare improve patient safety.